Development and Study of Demodulators for Frequency Hopping Spread Spectrum Signals - D. I. Kaplun; V. V. Gulvanskiy; I. I. Kanatov; D. M. Klionskiy; A. B. Khachaturyan; D. N. Butusov; V. F. Lapizkiy; V. I. Bobrovskiy (Известия высших учебных заведений России: Радиоэлектроника, 2017)
Demodulation task is encountered in many practical applications including digital signal processing and digital communications. Demodulation is connected with the communication system performance. Demodulation depends on a number of factors including signal-to-noise ratio (SNR) in the received message. In practice, it is necessary to minimize the number of errors for the given SNR and therefore new demodulation techniques are constantly developed with increased interference immunity. Demodulators aimed at for frequency-hopping spread spectrum signals have to meet special requirements since the message length can reach several ms and the number of messages can exceed several dozens.Frequency-hopping spread spectrum is a technique of information transmission via radio channel and it is distinguished by variable carrier frequency that can change many times. The carrier frequency changes according to a pseudo random number sequence, which is available to both a sender and a recipient. This technique improves interference immunity of a communication channel.Frequency-hopping spread spectrum is used in civil and special applications. This signal is stable to jamming (until the third side finds out the number sequence), which makes it possible to use it for special purposes (however, the signal still needs additional encryption).Demodulation includes signal detection, synchronization, message type determination (modulation speed and modulation type), decoding, determination of autostarting and autostop combinations (for message identification), composition of the received message. The paper considers the tasks beginning with message type determination.Message type determination can be carried out several ways: using the cross-correlation function, spectral analysis, etc. Since the structure of a synchrosequence is known, it is possible to obtain more precise results using the crosscorrelation function. Several synchrosequences are formed for each message and then we compute their cross-correlation with the received message. The analysis includes the comparison all the results of cross-correlation function computa-tion and finally we make a decision regarding the message.Determination of autostarting and autostop combinations is performed by comparing autostarting and autostop combinations from the database. Each autostarting combination determines the receiver operation mode (single-channel or frequency-hopping spread spectrum). Determination of combinations is performed during signal demodulation.Reception of a frequency-hopping spread spectrum signal is performed according to the frequency plan. According to this plan, the carrier frequency changes in fixed time points. After receiving the autostarting combination of frequencyhopping spread spectrum, a reception mode for frequency-hopping spread spectrum signal is switched on. After receiving the autostop combination this mode is terminated. The output of a demodulator is the message itself, modulation type, and carrier frequency.The outcome of demodulator performance can be represented with a table. The first column of this table contains the carrier frequency, the second column contains frequency deviation, the third column - modulation type, the fourth one - message speed, the fifth one and further - the message itself.In the paper, we provide new demodulation techniques of frequency-modulated messages for the given SNR. The developed techniques are based on spectral analysis and correlation analysis. We determine the computational complexity of the developed demodulation techniques. The total error is computed for each SNR and the selected demodulation technique using the developed MATLAB/Simulink model for a communication channel. Finally, we conclude about the best demodulation technique for the selected message type for the given SNR.